The relationship between the history of low birth weight babies and the growth and development of children 1-2 years old - Rodliya, Adzka Fahma; Dhiani, Dysa Noor; Pertiwi, Mumpuni Intan (Sekolah Tinggi Ilmu Kesehatan Harapan Ibu Jambi, 2025)
Background: The World Health Organization (WHO) estimates that 15% to 20% of all births worldwide are low birth weight (LBW) births, representing more than 20 million per year. LBW causes asphyxia, hypothermia, infection and growth and development disorders. This study aims to see the extent of the risk of growth and development disorders in children with a history of LBW. Method: Methods in this study used an observational retrospective cohort design. The affordable population in this study were children aged 1-2 years in the working area of Puskesmas Wates. For children who had a history of LBW samples taken by purposive sampling and for children who had a history of normal birth weight samples taken by accidental sampling with samples of 70 respondents. Data obtained from KIA book, KMS card and the results of measuring results development used KPSP. Data analysis used chi-square test. Results: 65.7% of children aged 1-2 years with a history of LBW experienced growth and development disorders, while 28.6% of children aged 1-2 years with a history of LBW experienced growth disorders and 31.4% experienced development disorders. Statistical tests obtained a p-value of growth = 0.002 and relative risk (RR) = 2.3 (95% CI 1.293-4.091). Statistical tests obtained a p-value of development = 0.004 and relative risk (RR) = 2.1 (95% CI 1.213-3.605). Conclusion: The conclusion of this study shows that children aged 1-2 years with a history of LBW are 2.3 times more likely to experience growth disorders and 2.1 times more likely to experience developmental disorders.